Личностно-ориентированная стратегия обучения как условие создания безопасного образовательного пространства - Каменева И. Ю. (Психологически безопасная образовательная среда: проблемы проектирования и перспективы развития, 2020)
the article describes the use of student-centered learning strategies for creating a safe learning space, highlights the capabilities of the person-oriented approach compared to a traditional knowledge-oriented approach, identifies threats and risks of personal safety of students, marks protective potential of personality-oriented educational space. The article also considers the specifics of the teacher's position in the personal-oriented educational space, the role of the teacher in ensuring the personal safety of students in the educational space.
Keywords: educational space; personal development; value system; personal security